PENGARUH ACCOUNT REPRESENTATIVE (AR) TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (KPP PRATAMA SIDOARJO UTARA) - ALFIANSYAH, FEBRI (Jurnal Akuntansi AKUNESA, 2012)
This research aims to determine whether there is influence between the Account Representative (AR) to an individual taxpayer compliance. Statistical methods used in this study is a simple linear regression analysis. Data were obtained through questionnaires and interviews with individual taxpayers as respondents in the “KPP Pratama Sidoarjo Utara”. The results showed that the existence of Account Representative (AR) affects an individual taxpayer compliance. Effect of Account Representative (AR) can be categorized in the category of